The mTOR-S6K pathway links growth signalling to DNA damage response by targeting RNF168 - Xie, Xiaoduo; Hu, Hongli; Tong, Xinyuan; Li, Long; Liu, Xiangyuan; Chen, Min; Yuan, Huairui; Xie, Xia; Li, Qingrun; Zhang, Yuxue; Ouyang, Huafang; Wei, Mengqi; et al. (Nature cell biology, 2018)
Growth signals, such as extracellular nutrients and growth factors, have substantial effects on genome integrity; however, the direct underlying link remains unclear. Here, we show that the mechanistic target of rapamycin (mTOR)-ribosomal S6 kinase (S6K) pathway, a central regulator of growth signalling, phosphorylates RNF168 at Ser60 to inhibit its E3 ligase activity, accelerate its proteolysis and impair its function in the DNA damage response, leading to accumulated unrepaired DNA and genome instability. Moreover, loss of the tumour suppressor liver kinase B1 (LKB1; also known as STK11) hyperactivates mTOR complex 1 (mTORC1)-S6K signalling and decreases RNF168 expression, resulting in defects in the DNA damage response. Expression of a phospho-deficient RNF168-S60A mutant rescues the DNA damage repair defects and suppresses tumorigenesis caused by Lkb1 loss. These results reveal an important function of mTORC1-S6K signalling in the DNA damage response and suggest a general mechanism that connects cell growth signalling to genome stability control.